Viking's season: That rush to get them / Interactivity: A four-axes slapskate / Interraps still loves to innovate / A slapshoe should be different, too! / The FINN clap skate mechanism - ZZZ(Klappschlittschuh) (Speedskating World, 1997)
Mehrere Beiträge, die sich mit verschiedenen Seiten der Problematik "Klappschlittschuh" beschäftigen, insbesondere dem Aufbau, der Mechanik und den Herstellern.